The Polysemy of Compound Words in Uzbek and English - qizi, Ziyodullayeva Marjona Habibullo (International Journal on Integrated Education, 2023)
In this article, the polysemy of compound words in Uzbek and English, the polysemy of phraseological units in Uzbek and English, several meanings of polysemantic phraseological units, the appearance of a lexeme denoting a person in an indicative agreement, in the first sense, all three persons pave the way for the use of a numerical relative , parts of compound words are obsolete compared to the modern language or borrowed from other languages, simple words that cannot be divided into meaningful parts in the current language, compound words are divided into meaningful parts, and each is written that phraseological units in one language have their own linguistic properties, and that phraseological units in all languages serve as linguistic wealth, and polysemantic phraseological units make up the lexical structure and speech of the language.